Orographic effect in a transparent between Fundão and Santa Teresa, Espírito Santo in the hydrological year 2015/2016 - Nascimento, Fabricio Holanda do; do Vale, Cláudia Câmara (Geografares, 2019)
This paper aims to evaluate the spatial distribution of rainfall in an 18.8 km transect by means of experimental rain gauges. For that, seven experimental pluviometers were made, through a 100 mm PVC pipe and a 500 ml beaker to collect the data. The rain gauges were installed along the state highway Josil Espíndula (ES 365), between the municipalities of Fundão and Santa Teresa, Espírito Santo state. For the installation of the same were considered some factors: different altitudes, locations with little vegetation cover and in backyards of residents, to avoid damaging the equipment by on-site passersby. The methodology used was satisfactory, since it allowed to identify that the morphology and the characteristics of the site impose an unequal distribution of precipitation in the study area considered. This research presents itself as a pioneer in climate studies in Espírito Santo, and has not yet been done for other regions of the state.
Keywords: Relief; pluviometer; orographic rai; geographical climatology; Espirito Santo, Brazil